Sharafuddin Yunīni's Role in the Transmission of Ṣaḥīḥ Al-Bukhārī: A Critical Analysis of his Methodology and Contribution - Nishad, Muhammed (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
The appearance of al-Dajjāl and the descent of Masīḥ Īsā is an integral part of the Islamic beliefsystem according to the Last Day. Many debates have arisen around this topic generating argumentsand counter arguments among the scholers of Islam. Naturally, there are two parties holding theiropinions and providing scholarly evidences to support the stand. This study focuses on the MushkilahAḥadīth on the appearance of appearance of al-Dajjāl and the descent of Masīḥ Īsā, analysing thestandpoints of both proponents and opponents. It attempts to critically reveal the strength andweakness of each submission. And the researcher reaches into conclusion based on the analyticalstudy of Mushkilah Aḥadīth.